Development of Edutourism Media Based on Augmented Reality (AR) Tourism Bireuen Using Android-Based Screen - Rahmad, Rahmad; Fadhilah, Cut; Nunsina, Nunsina (Department of Informatics Faculty of Engineering Universitas Malikussaleh, 2024)
Increasing innovation and creativity in a product is an obligation. One of them is tourism media innovation. The latest innovation that is expected to attract people's attention is the application of Augmented Reality (AR) Technology on tourist attraction brochures through the screen. AR technology or can also be referred to as Augmented Reality is the integration of digital elements that are added to the real world and follow the existing environment. This application can be applied to android-based mobile devices. Thus, the cellphone screen will present a description of the tourist attraction and even display sound and video. Learning media through AR-based tourist object brochures as a smart, easy, fast solution to find out tourist objects in Bireuen Regency in an interesting way. Through an AR brochure, everyone can find out the tourist attractions in Bireuen Regency in real time.